The Application of Shear Wave Elastography in Clinical Practice - Cheng, Yitian; Liu, Boqin; Yu, Xinyi; Ma, Haoran; Chen, Yuanjie; Guo, Jiayi; Gui, Yawen; Zhang, Zhijun (International Journal of Public Health and Medical Research, 2025)
Shear wave elastography (SWE) is a novel type of ultrasound elastography technology that has emerged in recent years. It quantitatively measures the elastic modulus of tissues (represented by Young’s modulus values) by detecting the propagation speed of shear waves generated in tissues under the action of acoustic radiation force. SWE technology objectively reflects the hardness characteristics of tissues as an non-invasive and highly repeatable ultrasound examination method. It has significant advantages such as quantitative measurement, simple operation, and real-time dynamic imaging. As a result, it provides an important imaging evaluation tool for the early diagnosis of clinical diseases, pathological staging, and dynamic monitoring of treatment effects. With the continuous development of ultrasound technology and in-depth exploration of clinical applications, SWE technology has shown broad application prospects and important clinical value in multiple medical fields. This article systematically reviews the development history of ultrasound elastography technology, and focuses on elaborating the basic principles of SWE technology and its application status in clinical practice. Through a comprehensive analysis of the latest research progress at home and abroad, it elaborates on the research achievements and application value of SWE technology in multiple important clinical fields such as liver fibrosis assessment, thyroid nodule differential diagnosis, breast nodule benign and malignant discrimination, myocardial hardness detection, and kidney disease assessment. The aim is to provide comprehensive reference for clinical physicians and researchers, and to envision the future development direction of this technology.